2010
DOI: 10.1007/s00394-010-0099-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of antioxidants on postprandial oxidative stress and endothelial dysfunction in subjects with impaired glucose tolerance and Type 2 diabetes

Abstract: In diabetic subjects, altered glycaemia and lipaemia are closely correlated with markers of systemic oxidative stress. Our results show that the abnormal changes in oxidative-reductive balance parameters are paralleled by similar changes in markers of endothelial dysfunction and inflammation at 4 h after ingestion of a fatty meal. Supplementation with a pool of antioxidants can reduce oxidative stress and inflammation in healthy subjects and, more importantly, in IGT patients. This previous aspect suggests tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 38 publications
2
40
1
Order By: Relevance
“…Matsuo (2005) demonstrated that the use of this grain can also be beneficial for increasing the production of liver antioxidant enzymes. The increase of these enzymes is related with the reduction of harmful effects caused by free radicals on the human body, which it leads to a reduced endothelial alterations (endothelial dysfunction) and decreased oxidation of LDL-c molecules, and hence, reduces the risks for vascular diseases (ADLER et al, 2010;NERI et al, 2010;KUSIRISIN et al, 2009;GHIBU et al, 2008;JI et al, 2008). The present study also demonstrated that this pseudocereal positively influenced the various risk factors for the development of diabetes and vascular diseases, which are the most frequent diseases today.…”
Section: Discussionmentioning
confidence: 99%
“…Matsuo (2005) demonstrated that the use of this grain can also be beneficial for increasing the production of liver antioxidant enzymes. The increase of these enzymes is related with the reduction of harmful effects caused by free radicals on the human body, which it leads to a reduced endothelial alterations (endothelial dysfunction) and decreased oxidation of LDL-c molecules, and hence, reduces the risks for vascular diseases (ADLER et al, 2010;NERI et al, 2010;KUSIRISIN et al, 2009;GHIBU et al, 2008;JI et al, 2008). The present study also demonstrated that this pseudocereal positively influenced the various risk factors for the development of diabetes and vascular diseases, which are the most frequent diseases today.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial dysfunction constitutes a critical derangement in the pathogenesis of diabetic vascular disease (6,20,53). Current evidence indicates that enhanced vascular oxidative stress plays an important role in endothelial dysfunction (25,36). Endothelial activation is a hallmark of endothelial dysfunction and is characterized by enhanced proinflammatory cytokine and chemokine release as well as increased cellular adhesion molecule expression.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, development of targeted therapeutics is needed in order to ameliorate or eliminate diabetes associated kidney damage. In both experimental and clinical models of diabetes, antioxidants have been reported to reduce markers of oxidative stress [12,13]. Besides, some studies have showed that antioxidants are effective and cheaper than conventional therapy in management of some diseases [14].…”
Section: Introductionmentioning
confidence: 99%